G protein–coupled receptor kinase 2 and group I metabotropic glutamate receptors mediate inflammation‐induced sensitization to excitotoxic neurodegeneration. Issue 5 (14th March 2013) - Degos, Vincent; Peineau, Stéphane; Nijboer, Cora; Kaindl, Angela M.; Sigaut, Stéphanie; Favrais, Géraldine; Plaisant, Frank; Teissier, Natacha; Gouadon, Elodie; Lombet, Alain; Saliba, Elie; Collingridge, Graham L.; et al.
<x xml:space="preserve">Abstract</x> Objective The concept of inflammation‐induced sensitization is emerging in the field of perinatal brain injury, stroke, Alzheimer disease, and multiple sclerosis. However, mechanisms underpinning this process remain unidentified. Methods We combined in vivo systemic lipopolysaccharide‐induced or interleukin (IL)−1β–induced sensitization of neonatal and adult rodent cortical neurons to excitotoxic neurodegeneration with in vitro IL‐1β sensitization of human and rodent neurons to excitotoxic neurodegeneration. Within these inflammation‐induced sensitization models, we assessed metabotropic glutamate receptors (mGluR) signaling and regulation. Results We demonstrate for the first time that group I mGluRs mediate inflammation‐induced sensitization to neuronal excitotoxicity in neonatal and adult neurons across species. Inflammation‐induced G protein–coupled receptor kinase 2 (GRK2) downregulation and genetic deletion of GRK2 mimicked the sensitizing effect of inflammation on excitotoxic neurodegeneration. Thus, we identify GRK2 as a potential molecular link between inflammation and mGluR‐mediated sensitization. Interpretation Collectively, our findings indicate that inflammation‐induced sensitization is universal across species and ages and that group I mGluRs and GRK2 represent new avenues for neuroprotection in perinatal and adult neurological disorders. Ann Neurol 2013;73:667–678